PENEGAKAN HUKUM MELALUI RESTORATIVE JUSTICE YANG IDEAL SEBAGAI UPAYA PERLINDUNGAN SAKSI DAN KORBAN - Resti Dian Luthviati, Restika Prahanela, Prayogo Kurnia, (GEMA, 2015)
The victim in a crime, the National Legal System, its position is not profitable. Because these victims, the Justice System (Criminal), just as an extra, not as a main character or merely as a witness. Restorative justice puts a higher value on the direct involvement of the parties. The victim was able to restore control elements, while offenders are encouraged to take responsibility as a step in correcting errors caused by crime and in building social value system. Restorative justice approach is an approach that is more focused on the creation of conditions of fairness and balance to the criminal and the victim herself. This type of research used by the author in compiling this research is normative legal or legal research literature